Studies on Genetic Variability, Heritability and Character Association in Okra - Singh, A. P.; kumar, P. Pradeep; kumar, B. Ashok; Bahadur, V. (International Journal of Bio-resource and Stress Management, 2017)
The experiment was carried out at vegetable research farm, Department of Horticulture, Allahabad Agriculture Institute. The experimental materials for the present investigation consisted of 25 genotypes of okra. The experiment was laid out in a Randomized Complete Block Design with three replications. Five healthy plants were randomly selected from each plot for recording the sixteen important observations. The wide range of variability was observed among sixteen characters of all genotypes. The (PCV) were generally higher than their respective genotypic coefficient of variance, thus revealing the role of environmental factors. High PCV was reported by (%) disease incidence (77.04), fruit yield plant-1 (59.61), number of fruits plant-1 (56.15), number of branches plant-1 (37.23) and plant height (28.61). High heritability coupled with high genetic advance was observed for (%) disease incidence, fruit yield plant-1, number of fruits plant-1, plant height, number of locules plant-1 and fruit length. This indicated that these traits were under the strong influence of additive gene action and hence simple selection based on phenotypic performance of these traits would be more effective. In the present investigation character plant height (0.4464**), days to 50% harvesting (0.3181%), number of fruits plant-1 (0.9424**), number of seeds fruit-1 (0.2930*), fruit weight (0.2928*) and Vitamin C (0.4665) show positive significant phenotypic correlation with fruit yield plant-1. Positive direct effect number of branches plant-1 (0.9365), days to 50% flowering (0.1667), and number of fruits plant-1 (0.4650) and fruit length (0.1344) was main cause of their positive association with fruit yield plant at genotypic level.